Trend mahasiswa milenial dan perpustakaan: Studi kasus di Perpustakaan UIN Mataram - Nuraeni Nuraeni (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2021)
Millennial generation is gadget’s generation. The gadget’s generation use new technological innovations. We can find the gadget’s generation in university as millennial students.Five characteristics of millennial students; always using gadgets; prefer instant and fastfor everything; prefer to read in social media groups than on a bulletin board; no longer brings a pile of thick books to campus; starting to make lots of cashless transactions. UIN Mataram has accommodated the needs of millennial students, especially in library.The facilities and services that have provided the needs are by setting sockets in rooms; supplying free wifi; giving rooms for discussions; arranging space and adding flowers as accessories; simplifying any rules, and upgrading services by RFID technology.